Systematic Review of Valuation of State Property at the Indonesian State Property and Auction Service Office: Challenges and Successes - Jayadi, Yusma Indah; Irsyad, Muhammad (Asian Journal of Management Analytics, 2024)
This research focuses on the assessment of State Property (BMN) at the State Property and Auction Service Office (KPKNL). The Systematic Literature Review method was used using identified research questions consisting of PICO (Population, Intervention, Comparator, and Outcome). Case studies in several KPKNLs reveal that the role of work units has not been fully evaluated, the rental value calculation process has not been optimal, and BMN revaluation improvements have been successful despite facing obstacles. Although the assessment was carried out according to regulations, a need was found to address the lack of understanding of work units, optimize rental value calculations, and better time management. The BMN assessment at KPKNL is in accordance with regulations, but improvements are needed, including better understanding of work units, optimization of the rental value calculation process, and more efficient time management in BMN revaluation.